2015
DOI: 10.1111/jnc.13365
|View full text |Cite
|
Sign up to set email alerts
|

Cdk5 at crossroads of protein oligomerization in neurodegenerative diseases: facts and hypotheses

Abstract: Cyclin-dependent kinase 5 (Cdk5) is involved in proper neurodevelopment and brain function and serves as a switch between neuronal survival and death. Overactivation of Cdk5 is associated with many neurodegenerative disorders such as Alzheimer's or Parkinson's diseases. It is believed that in those diseases Cdk5 may be an important link between disease-initiating factors and cell death effectors. A common hallmark of neurodegenerative disorders is incorrect folding of specific proteins, thus leading to their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 158 publications
(286 reference statements)
0
38
0
Order By: Relevance
“…We found that injection of Aβ1‐42 monomers was followed by an increase (twofold) of pGSK3β protein levels (Fig. 4A) Then, we tested the levels of CDK5 a protein serine/threonine kinase (Wilkaniec et al ., 2016). As reported in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We found that injection of Aβ1‐42 monomers was followed by an increase (twofold) of pGSK3β protein levels (Fig. 4A) Then, we tested the levels of CDK5 a protein serine/threonine kinase (Wilkaniec et al ., 2016). As reported in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since neurodegenerative diseases share common features and mechanisms responsible for inducing the death of selective neuronal populations [ 49 51 ], the extracellular release of ASN as well as activation of P2 receptor may likely contribute, alone or in combination, to these mechanisms and to a neurodegenerative process. Purinergic signaling was previously shown to be involved in the etiopathology of many neurodegenerative disorders [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these genes, there were important transcription factors and kinases associated with AD including LEF1, SOX9, YY1, TCF3, TFDP1, CDK5, CSK and MAP3K3 . Among these genes, overactivation of CDK5 is a major trigger of tau hyperphosphorylation and NFT formation in AD suggesting it may be a target for therapeutic intervention (Wilkaniec et al, 2016). …”
Section: Network-based Approaches Identifies Pathways Specific To Alzmentioning
confidence: 99%